Fiscal Analysis of Resource Industries : (FARI Methodology) - Luca, Oana (Technical Notes and Manuals; Technical Notes and Manuals, 2016)
This manual introduces key concepts and methodology used by the Fiscal Affairs Department (FAD) in its fiscal analysis of resource industries (FARI) framework. Proper evaluation of fiscal regimes for extractive industries (EI) requires economic and financial analysis at the project level, and FARI is an analytical tool that allows such fiscal regime design and evaluation. The FARI framework has been primarily used in FAD's advisory work on fiscal regime design: it supports calibration of fiscal parameters, sensitivity analysis, and international comparisons. In parallel to that, FARI has also evolved into a revenue forecasting tool, allowing IMF economists and government officials to estimate the composition and timing of expected revenue streams from the EI sector, analyze revenue management issues (including quantification of fiscal rules), and better integrate the EI sector in the country macroeconomic frameworks. Looking forward, the model presents a useful tool for revenue administration practitioners, allowing them to compare actual, realized revenues with model results in tax gap analysis.